Effect of Electrokinetic Remediation on the Distribution and Concentration of Lead (Pb) in Ex-Mining Land of PT Semen Baturaja Tbk - Rahma Nur Komariah; Achmad Chalid Afif Alfajrin; Arien Aisyara; Muhammad Akmal Halid; Lamtongam Simatupang; Hamzah Daffa Ghifari; Hendra Prasetia; Angga Jati Widiatama; Sabar Sabar; Rhahmi Adni Pesma; Rezki Naufan Hendrawan; Fadli Hastito (Universitas Andalas, 2026)
Mining activities can lead to the accumulation of heavy metals in soil, particularly lead (Pb), which poses risks to ecosystems and human health. PT Semen Baturaja Tbk has implemented revegetation as a post-mining reclamation strategy, but the success rate remains low, potentially due to high Pb concentrations in the soil. This study investigates the effectiveness of electrokinetic remediation in mobilizing Pb ions in ex-mining soil using aluminum electrodes under a 20 V direct current over treatment durations of 24 and 48 hours. Soil moisture was maintained at 900 ml, and Pb concentrations were measured using X-Ray Fluorescence (XRF). The results indicate that Pb²⁺ ions migrated towards the cathode, with a significant accumulation observed after 48 hours. However, an increase in Pb concentration near the anode was also detected, likely due to Pb oxidation at the anode plate, leading to remobilization of Pb into the soil. These findings highlight both the potential and limitations of electrokinetic remediation for in-situ heavy metal removal in post-mining land reclamation.